HbA1c variability is associated with increased mortality and earlier hospital admission in people with Type 1 diabetes. Issue 11 (11th September 2017) - Walker, G. S.; Cunningham, S. G.; Sainsbury, C. A. R.; Jones, G. C.
Abstract: Aim: Despite evidence of morbidity, no evidence exists on the relationship between HbA1c variability and mortality in Type 1 diabetes. We performed an observational study to investigate whether the association between HbA1c variability and mortality exists in a population of people with Type 1 diabetes. As a secondary outcome, we compared onset of first hospital admission between groups. Methods: People with Type 1 diabetes were identified for inclusion from the Scottish Care Information – Diabetes data set. This database includes data of all people known to have diabetes who live within Scotland. A survival analysis was carried out over a 47‐month period comparing two groups; group 1 with a HbA1c coefficient of variation (CV) above the median CV value, and group 2 with a CV below the median value. Time to death or first admission was also analysed. A Cox proportional hazard model was used to compare time to death, adjusting for appropriate covariables. Results: Some 6048 individuals with Type 1 diabetes were included in the analysis. Median HbA1c CV was 7.9. The hazard ratio (HR) for mortality for those with an HbA1c CV above the median value is 1.5 over 47 months of follow‐up ( P  < 0.001). HR for survival to either the first admission to hospital or death for those with an HbA1c CV above the median value was 1.35 (95% confidence interval 1.25–1.45) over 730 days of follow‐up ( P  < 0.001). Conclusion: Our results show that people with greater HbA1c variability have a higher rate of mortality and earlier hospital admission in Type 1 diabetes. What's new?: HbA1c variability is known to be associated with mortality in Type 2 diabetes. This is the first study to show an association between HbA1c variability and mortality in Type 1 diabetes. Our data also show an association between HbA1c variability and the combined end‐point of death or first admission to hospital. HbA1c variability could be a useful clinical marker of risk in people with Type 1 diabetes.